MOST IMPORTANT INVENTIONS AND FUTURE TECHNOLOGY IDEAS - Muxtarov Abduvali; To`raxon Abdurahmonov (TADQIQOTLAR, 2026)
Abstract Technological development has played a crucial role in shaping human civilization from ancient times to the modern digital age. Throughout history, inventions have helped humanity overcome challenges, improve living standards, and expand knowledge. The rapid development of science and engineering in the last few centuries has resulted in groundbreaking innovations that transformed industries, economies, and societies. Today, the pace of technological progress continues to accelerate, creating new opportunities as well as challenges for humanity. This thesis explores the most important inventions that have significantly influenced human development and examines modern technological advancements that are shaping the present world. In addition, the research analyzes future technology ideas that scientists and engineers believe will transform society in the coming decades. By studying historical inventions and emerging technologies, we can better understand how innovation drives progress and how societies can adapt to technological change. Organizations such as MIT Technology Review and World Economic Forum continuously analyze technological trends and provide insights into the future of global innovation. Their research highlights the importance of investing in science, education, and research in order to create sustainable development and economic growth. This thesis aims to provide a comprehensive understanding of technological evolution, its impact on society, and the potential direction of future innovations.